Photocatalytic Protein Damage by Silver Nanoparticles Circumvents Bacterial Stress Response and Multidrug Resistance - Shi, Tianyuan (mSphere, 2019)
Silver nanoparticles (AgNPs) are known for their broad-spectrum antibacterial properties, especially against antibiotic-resistant bacteria. However, the bactericidal mechanism of AgNPs remains unclear. In this study, we found that the bactericidal ability of AgNPs is induced by light. In contrast to previous postulates, visible light is unable to trigger silver ion release from AgNPs or to promote AgNPs to induce reactive oxygen species (ROS) in Escherichia coli. In fact, we revealed that light excited AgNPs to induce protein aggregation in a concentration-dependent manner in E. coli, indicating that the bactericidal ability of AgNPs relies on the light-catalyzed oxidation of cellular proteins via direct binding to proteins, which was verified by fluorescence spectra. AgNPs likely absorb the light energy and transfer it to the proteins, leading to the oxidation of proteins and thus promoting the death of the bacteria. Isobaric tags for relative and absolute quantitation (iTRAQ)-based proteomics revealed that the bacteria failed to develop effective resistance to the light-excited AgNPs. This direct physical mechanism is unlikely to be counteracted by any known drug resistance mechanisms of bacteria and therefore may serve as a last resort against drug resistance. This mechanism also provides a practical hint regarding the antimicrobial application of AgNPs—light exposure improves the efficacy of AgNPs. IMPORTANCE Although silver nanoparticles (AgNPs) are well known for their antibacterial properties, the mechanism by which they kill bacterial cells remains a topic of debate. In this study, we uncovered the bactericidal mechanism of AgNPs, which is induced by light. We tested the efficacy of AgNPs against a panel of antimicrobial-resistant pathogens as well as Escherichia coli under conditions of light and darkness and revealed that light excited the AgNPs to promote protein aggregation within the bacterial cells. Our report makes a significant contribution to the literature because this mechanism bypasses microbial drug resistance mechanisms, thus presenting a viable option for the treatment of multidrug-resistant bacteria.